Asas Itikad Baik Dalam Lelang Eksekusi Hak Tanggungan (Studi Putusan Nomor 375/PDT/2023/PT DKI) - Febiola Efendi Putri Sormin, Anggelika; Suhermi, Suhermi; Manik, Herlina (Zaaken: Journal of Civil and Business Law, 2026)
This research aims to determine and analyze the legal regulations regarding the principle of good faith in the execution auction of mortgage rights according to the Indonesian legal system, as well as the considerations of the Panel of Judges in Decision Number 375/PDT/2023/PT DKI in assessing the application of the principle of good faith in the execution auction of mortgage rights. The method employed is normative legal research, utilizing a statutory approach, a case approach, and a conceptual approach. The research results indicate that the principle of good faith in the execution auction of mortgage rights is not only regulated in Article 1338 paragraph (3) of the Civil Code, but also in the Mortgage Law, the Banking Law, the Minister of Finance Regulation, and SEMA Number 4 of 2016. However, its application still heavily relies on the judicial interpretation. Decision Number 375/PDT/2023/PT DKI affirms that a buyer of an auctioned property who is aware of a dispute is not a bona fide purchaser; thus, the auction is declared void. Conversely, at the appellate levels, the Supreme Court considered that the auction procedure was in accordance with regulations and that the auction buyer was considered a bona fide purchaser. This difference in consideration shows the inconsistency of Judges in applying the principle of good faith. This research suggests that the parameters of the principle of good faith include compliance with procedures and legal regulations, transparency of information regarding the legal status of the auctioned object, and prohibition against profiting from the disadvantages of other parties.